1985
DOI: 10.1210/endo-117-1-141
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Photoperiod Alter the Daily Rhythms of Pineal Melatonin Content and Hypothalamicβ-Endorphin Content and the Luteinizing Hormone Response to Naloxone in the Male Syrian Hamster*

Abstract: This study examines the possible involvement of beta-endorphin in the photoperiodic control of reproduction in the Syrian hamster. beta-Endorphin and LHRH concentrations in the medial basal hypothalamus (MBH), anterior hypothalamus (AHA), and the preoptic area (POA) as well as pineal melatonin content were determined by RIA in male Syrian hamsters exposed to either a long day [(LD) 16-h light; 8-h dark; lights on 0700-2300] or short day [(SD) 8-h light, 16-h dark; lights on 0700-1500] for 8 weeks. Groups of ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
37
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 42 publications
8
37
0
Order By: Relevance
“…Contrary to what has been claimed for some time Rollag et al, 1980 ;Tamarkin et al, 1980) this also appears to be true in the Syrian hamster (Roberts et al, 1985 ;Skene et al, 1987). Similar data were also obtained in the sheep (review in Arendt, 1986) Recently this hypothesis has been further elaborated and two models, the internal coincidence and the external coincidence ones, being proposed (Reiter, 1987b).…”
mentioning
confidence: 70%
“…Contrary to what has been claimed for some time Rollag et al, 1980 ;Tamarkin et al, 1980) this also appears to be true in the Syrian hamster (Roberts et al, 1985 ;Skene et al, 1987). Similar data were also obtained in the sheep (review in Arendt, 1986) Recently this hypothesis has been further elaborated and two models, the internal coincidence and the external coincidence ones, being proposed (Reiter, 1987b).…”
mentioning
confidence: 70%
“…As other mammalian species investigated so far (Bittman et al, 1983 ;Roberts et al, 1985), we have observed the diurnal changes in melatonin secretion in goats, which are synchronized with light-dark cycles . The following experiments were conducted to determine the role of the pineal gland in the mechanism regulating the seasonal change in gonadal activity and the prolactin secretion.…”
Section: Introductionmentioning
confidence: 96%
“…The hypothalamic P-EP concentration has also been shown to fluctuate with a diurnal rhythm, demonstrating a significant nocturnal increase [8][9][10], abolished by the suppression of the dark phase of the day-night cycle [10].…”
mentioning
confidence: 99%